(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The nature of modern threats poses serious challenges to national security systems. They are forced to undergo transformations with high intensity and structural impact in order to adapt to the security environment. The iterative nature of the problem and the constantly changing context of its updating necessitate the study of the structural and functional integrity of national security systems. The report presents a methodology for assessing a proposed model of a national security system, in the sense of a set of management bodies and their functions. To achieve the goal, generally accepted methods of analysis were used: system analysis (structural, functional), analysis and synthesis, induction and deduction, mathematical modeling, criterial analysis and risk analysis methods. The results obtained are a summary of independently conducted expert assessments of the proposed model, based on criteria that represent the objective state of the system. They include recommendations for improving: the attainability of the goals, the adequacy of the structure and functions of the model.